An Outline History of East Asia to 1200 - Schneewind, Sarah (Open textbook library., 2020)
This is the second edition of the open access textbook that arose out of a course at the University of California, San Diego, called HILD 10: East Asia: The Great Tradition. The course covers what have become two Chinas, Japan, and two Koreas from roughly 1200 BC to about AD 1200. As we say every Fall in HILD 10: “2400 years, three countries, ten weeks, no problem.” The book does not stand alone: the teacher should assign primary and secondary sources, study questions, dates to be memorized, etc. The maps mostly use the same template to enable students to compare them one to the next. The 1st edition is in the supplemental material tab.